2007
DOI: 10.1007/s00500-007-0186-7
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic time series forecasting using fuzzy recurrent neural network

Abstract: It is known that one of the most spread forecasting methods is the time series analysis. A weakness of traditional crisp time series forecasting methods is that they process only measurement based numerical information and cannot deal with the perception-based historical data represented by linguistic values. Application of a new class of time series, a fuzzy time series whose values are linguistic values, can overcome the mentioned weakness of traditional forecasting methods. In this paper we propose a fuzzy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Aliev et al, 2008, have proposed, fuzzy recurrent neural network (FRNN) based time series forecasting method for solving forecasting problems, in an experiment and they found that the performance of the proposed method for forecasting fuzzy time series shows its high efficiency and effectiveness for a wide domain of application areas ranging from weather forecasting to planning in economics and business [67]. In 2001 Luk et al, have developed and compared three types of ANNs suitable for rainfall prediction i.e.…”
Section: Other Methodsmentioning
confidence: 99%
“…Aliev et al, 2008, have proposed, fuzzy recurrent neural network (FRNN) based time series forecasting method for solving forecasting problems, in an experiment and they found that the performance of the proposed method for forecasting fuzzy time series shows its high efficiency and effectiveness for a wide domain of application areas ranging from weather forecasting to planning in economics and business [67]. In 2001 Luk et al, have developed and compared three types of ANNs suitable for rainfall prediction i.e.…”
Section: Other Methodsmentioning
confidence: 99%
“…In another experiment HartmNeural Network et al, 2007, have found that the neural network algorithms are capable of explaining most of the rainfall variability even it can predict the summer rainfall also [66]. Aliev et al, 2008, have proposed, fuzzy recurrent neural network (FRNN) based time series forecasting method for solving forecasting problems, in an experiment and they found that The performance of the proposed method for forecasting fuzzy time series shows its high efficiency and effectiveness for a wide domain of application areas ranging from weather forecasting to plNeural Networking in economics and business [67]. , have worked out to find out best hidden layer size for three layered neural net in predicting monsoon rainfall in India, and they have found that eleven-hidden-nodes three-layered neural network has more efficacy than asymptotic regression in the present forecasting task [68].…”
Section: Comprehansive Literature Review 21 Rainfall Predictionmentioning
confidence: 99%
“…An artificial neural network model was developed to predict 1 to 6-hours-ahead rainfall at 75 rain gauge stations using the data of 3 consecutive years and it could be also used in real time rain forecasting and flood management [7]. The application of fuzzy recurrent neural network in many areas including rainfall forecasting was shown by in [8].…”
Section: Related Workmentioning
confidence: 99%